Elektroniskās komercijas analīze pircēju rīcības kontekstā. - Bergs, Raivis (Latvijas Universitāte, 2019)
Darba mērķis ir pamatojoties uz teorētiskām atziņām, iedzīvotāju aptaujas un intervijas rezultātiem, izpētīt elektronisko komerciju pircēju rīcības kontekstā, atklāt nepilnības un sniegt ieteikumus to novēršanai. Pirmā nodaļā tiks raksturota elektroniskā komercija, tās attīstība, veidi. Otrajā nodaļā tiks apkopotas elektroniskajā komercijā iesaistīto pušu pircēju un pārdevēju rīcības īpatnības. Trešajā nodaļā tiks analizēta tiešsaistes veikalu attīstība pasaulē un Latvijā. Ceturtajā nodaļā tiks apkopoti aptaujas un intervijas rezultāti. Darba beigās apkopoti secinājumi un sniegti priekšlikumi. Darba apjoms -105 lappuses,ir iekļautas 8 tabulas, 42 attēli un 12 pielikumi.

The aim of the research is to explore the electronic commerce in the context of buyers’ behaviour basing on theoretical works, public survey and interviews in order to discover the shortcomings and to provide correcting recommendations or improvement. The first chapter deals with the electronic commerce, its development and typology. The second chapter summarizes the features of the stakeholders (buyers and sellers) of the electronic commerce. The third chapter analyses the development of online shops in the world and in Latvia. The fourth chapter aggregates the customer survey and interview data. The final part of the research draws the conclusions and provides recommendations for improvement. The hypothesis of the research – low prices, time saving opportunities and wide-ranged offers stimulate the activity of Latvian customers in the online shops, meanwhile the incompliance of the product to its description and picture impedes it – is partially confirmed. Scope of the study is 105 pages, 8 tables, 42 figures and 12 appendices.
Analysis of e-commerce in the context of customer behavior.
Keywords: Vadībzinātne; veikals; e-komercija; consumer behavior; online shop; services